Accurate determination of glomerular filtration rate in adults for carboplatin dosing: Moving beyond Cockcroft and Gault. (March 2021) - Tsang, Corey; Akbari, Ayub; Frechette, Dominque; Brown, Pierre Antoine
Objective: Carboplatin is a cytotoxic chemotherapy drug developed in the 1980s which is still widely used today across various tumour types. Despite its common application, there remains a significant controversy and practice variation on its unique method of dosing by area under the curve (AUC). One potential reason for this variability stems from the reliance of using an estimated glomerular filtration rate (eGFR) as an extrapolation of the measured GFR (mGFR) which the commonly used Calvert equation was originally validated for. This review takes a novel and collaborative nephro-oncology approach to highlight the historical evolution of carboplatin dosing, methods for estimating GFR and its relative performance in the application of carboplatin dosing for adult patients. Data sources: We reviewed all pertinent publications comparing carboplatin AUC-based dosing in adult patients based on the various methods of GFR measurements or estimations in order to provide a comprehensive description of each method's advantages and risks. Data summary and conclusions: The Cockcroft-Gault equation has been widely studied but newer eGFR equations, such as the CKD-Epidemiology Collaboration (CKD-EPI) or Janowitz-Williams equation have outperformed the Cockcroft-Gault in recent studies.